Gene Targeting in the Red Alga Cyanidioschyzon merolae: Single- and Multi-Copy Insertion Using Authentic and Chimeric Selection Markers - Fujiwara, Takayuki; Ohnuma, Mio; Yoshida, Masaki; Kuroiwa, Tsuneyoshi; Hirano, Tatsuya (PLOS ONE, 2013)
The unicellular red alga Cyanidioschyzon merolae is an emerging model organism for studying organelle division and inheritance: the cell is composed of an extremely simple set of organelles (one nucleus, one mitochondrion and one chloroplast), and their genomes are completely sequenced. Although a fruitful set of cytological and biochemical methods have now been developed, gene targeting techniques remain to be fully established in this organism. Thus far, only a single selection marker, URACm-Gs, has been available that complements the uracil-auxotrophic mutant M4. URACm-Gs, a chimeric URA5.3 gene of C. merolae and the related alga Galdieria sulphuraria, was originally designed to avoid gene conversion of the mutated URA5.3 allele in the parental strain M4. Although an early example of targeted gene disruption by homologous recombination was reported using this marker, the genome structure of the resultant transformants had never been fully characterized. In the current study, we showed that the use of the chimeric URACm-Gs selection marker caused multicopy insertion at high frequencies, accompanied by undesired recombination events at the targeted loci. The copy number of the inserted fragments was variable among the transformants, resulting in high yet uneven levels of transgene expression. In striking contrast, when the authentic URA5.3 gene (URACm-Cm) was used as a selection marker, efficient single-copy insertion was observed at the targeted locus. Thus, we have successfully established a highly reliable and reproducible method for gene targeting in C. merolae. Our method will be applicable to a number of genetic manipulations in this organism, including targeted gene disruption, replacement and tagging.